Analysis of Nagari Go Digital Innovation as An Improvement in Population Administration Services by The Population and Civil Registration Office of Padang Pariaman Regency - Resti Fajria; Roni Ekha Putera; Ria Ariany (Department of Public Administration, 2023)
Padang Pariaman Regency has 103 nagari spread and has access to different geographical conditions. So that this affects services in population administration and civil registration which makes people reluctant to take care of it for reasons that access is quite difficult to reach. As one of the efforts to improve public services, the Population and Civil Registration Office of Padang Pariaman Regency created an innovation Nagari Go Digital. This research was designed using qualitative methods with a descriptive approach. The purpose of this study is to analyze the Nagari Go Digital program in improving public services in Padang Pariaman Regency. The results of this study show that the innovation of the Nagari Go Digital program can increase the effectiveness of the implementation of population document services held in the Nagari government with the support of digital services. So that it has benefits for the community in obtaining services without having to come to the office of the Population and Civil Registration Office. However, there are still some obstacles that occur in Nagari as an implementing organization so that it needs to be improved again in its implementation